Riesz bases of exponentials for convex polytopes with symmetric faces - Debernardi, Alberto (2022)
We prove that for any convex polytope $Ω\subset \mathbb{R}^d$ which is centrally symmetric and whose faces of all dimensions are also centrally symmetric, there exists a Riesz basis of exponential functions in the space $L^2(Ω)$. The result is new in all dimensions $d$ greater than one.